(untitled) (Slavic Studies, 2024)
The research is dedicated to the short narrative forms in the work of Olga Tokarchuk, thorugh theanalysis the short story "The Wardrobe". The interpretation is based on concepts that determine the aesthetics and ethics of the author’s narrative such as: tenderness, care, authentic relationship and connections.